A Meta-Analysis of miR-499 rs3746444 Polymorphism for Cancer Risk of Different Systems: Evidence From 65 Case-Control Studies - Yang, Xianglin; Li, Xuelian; Zhou, Baosen (Frontiers in Physiology, 2018)
MicroRNAs (miRNAs) are a class of endogenous, short and non-coding RNAs that may play important roles in the pathogenesis of tumor. The associations between microRNA-499 rs3746444 polymorphism and cancer risk in different systems remain inconclusive. This article is aimed to obtain more exact estimation of these relationships through a meta-analysis based on 52456 individuals. We retrieved relevant and eligible studies from Pubmed and Embase database up to January 10, 2018. ORs and 95% CIs were used to estimate the associations between miR-499 polymorphism and cancer susceptibility in different systems. All analyses were performed using the Stata 11.0 software. A total of 65 case-control studies were retrieved using explicit inclusion and exclusion criteria. The study included 23762 cases and 28694 controls. Overall cancer analysis showed the association between miR-499 polymorphism and susceptibility to cancer was significant. MicroRNA-499 rs3746444 was found to be significantly associated with increased risk of cancer of the respiratory system (CC vs.TT: OR = 1.575, 95% CI = 1.268-1.955, CC vs. TC+TT: OR = 1.527, 95% CI = 1.232-1.892), digestive system (CC vs.TT: OR = 1.153, 95% CI = 1.027-1.295; TC vs. TT: OR = 1.109, 95% CI = 1.046-1.176; CC+TC vs. TT: OR = 1.112, 95% CI = 1.018-1.216; CC vs. TC+TT: OR = 1.137, 95% CI = 1.016-1.272; C vs. T: OR = 1.112, 95% CI = 1.025-1.206), urinary system (TC vs. TT: OR = 1.307, 95% CI = 1.130-1.512; CC+TC vs. TT: OR = 1.259, 95% CI = 1.097-1.446; C vs. T: OR = 1.132, 95% CI = 1.014-1.264), and gynecological system (C vs. T: OR = 1.169, 95% CI = 1.002-1.364). In the subgroup analysis by ethnicity, the result showed that significant association with an increased cancer risk was found in Asian. Subgroup analysis based on type of tumor was also performed, miR-499 rs3746444 is associated with susceptibility of cervical squamous cell carcinoma, lung cancer, prostate cancer, and hepatocellular carcinoma.